المستجدات في مسؤولية الدولة عن أعمال السلطة التشريعية (دراسة تحليلية مقارنة) (مستل) - سعيد, دانا عبدالكريم; عزالدين, هاوسەر نورالدين (Sulaimani Journal for Humanities, 2022)
At the beginning, the state was not being held responsible for the acts ofthe legislature, stickingto a conventional principle that purports that the state. Is not responsible for the acts of its authorities. This was reverting to the notion of sovereignty, being viewed as something incompatible with the principle of responsibility, as it was thought that the principles ofsovereignty and responsibility can never meet. The state, having sovereignty can never be held responsible for its acts. This tenet remained dominant until the end of the later nineteenth century. Consequent was impossible for the aggrieved party who was impinged by the acts of the legislature (Laws and parliamentary acts) to ask for compensation. This stirred the jurists who called for constituting the redress upon various bases and standards. This was parallel with a development that thejudgment of administrative justice witnessed, as it took a different attitude as compared to the past. Due to the recent efforts and ruling of justice which endeavored to adopt this responsibility, even in the possible narrowest scheme, in addition to the weakness and vulnerability of the arguments and the supportive proof that was defending the irresponsibility of the state for the acts of legtheislature, so another trend evolved. This trend was aiming at alleviating the rigidity of the “irresponsibility tenet “through creating some exceptions on the general principle, i.e the non-responsibility of the state for legislature acts.